"Deep approaches to learning" in a project‐based nanofabrication graduate course. Issue 2 (24th October 2022) - Tang, Mary; Kommera, Swaroop; Raghuram, Usha; Rincon, Michelle; Xu, Xiaoqing; Fan, Jonathan; Howe, Roger T.
Abstract: We describe a graduate‐level, laboratory course that is structured as a "master class" in experimental research project planning and execution. Students work in teams to engage in project topics of their choosing, ideally relevant to their own areas of research, that make use of the university's shared fabrication and characterization facilities. After developing their project plans, which includes a schedule, budget, and milestones, students execute them under the guidance of their mentors. The aim of the course is that the students develop deep conceptual knowledge of the practice of experimental science, with regard to: project planning and execution, effective communication and teamwork, technical rigor, and peer review. Because students learn by applying these skills to topics that are personally relevant to them, this course can be described as using on deep approaches to learning. Abstract : We describe a laboratory course designed as a "master class" in experimental research project planning and execution. Students work in teams under the guidance of mentors to set the schedule, budget, and milestones and thus develop a deep, conceptual understanding of best practices in experimental science. Project results, including SOPs ("nano nuggets"), are made available to the public.